Numerical analysis of hydraulic operation conditions for a selected water supply system - Kępa, Urszula (Instal, 2023)
The article presents an analysis of a water supply network designed to deliver water to small settlement unit. The impact of selected pipe diameters on the operation of a small network system was determined. The calculated maximum water hourly demand for the perspective period, was equal to Qhmax=2.83 dm³/s. The demand for water for fire protection purposes was determined based on the “Regulation of the Minister of Interior and Administration of July 24, 2009 on fire water supply and fire roads” (original: “Rozporządzeniem Ministra Spraw Wewnętrznych i Administracji z dnia 24 lipca 2009 r w sprawie przeciwpożarowego zaopatrzenia w wodę oraz dróg pożarowych”) in the amount of Qfire = 5.0 dm³/s. The total length of the network was 2309 m, and the network consisted of three distribution lines (rays). The network operating conditions were analysed for two cases of selected diameters. In the first case, the diameters of the pipes were in compliance with the Regulation. In the second, the diameters of the pipes were selected to obtain the required minimum water flow rates. At the same time, the pressure losses occurring in both cases were compared. The network operation was also analysed with only flows for domestic purposes, without the fire protection flows, in conditions that usually prevail during operation. The hydraulic model of the network made in the Epanet 2 program was used for the analysis. Based on the analysis, it was found that in the case of small, new water supply systems, the applicable legal regulations force usage of pipes with excessively large diameter. Velocity of water flow in the network during normal operation is well below the minimum required value of 0.5 m/s. Water supply networks then require increased maintenance and are not used to their full extent. It should be allowed for small water systems to use pipelines with smaller diameter, similarly to the expansion of water supply systems. This would require a full hydraulic analysis of the designed network, for example using hydraulic modelling.
Keywords: water supply network; design; operation; small settlement units